Characterizing the shape and heat production of open vertical cracks in burst vibrothermography experiments. (March 2019) - Mendioroz, A.; Martínez, K.; Celorrio, R.; Salazar, A.
Abstract: We present a quantitative characterization of the heat flux distribution generated at open vertical cracks in burst vibrothermography experiments. We use a stabilized inversion algorithm that is able to retrieve both homogeneous and inhomogeneous fluxes from surface temperature data generated by open cracks. The performance of the algorithm is checked by inverting both synthetic data with added random noise and experimental data taken on samples containing calibrated heat sources. The results show that it is possible to characterize simultaneously the geometry and the absolute value of the heat flux distribution generated at the crack and therefore, the total emitted thermal power. Highlights: We characterize the area where heat is produced at open cracks in burst vibrothermography. We obtain the absolute heat flux distribution generated at cracks in burst vibrothermography experiments. The total thermal power generated at the crack is determined.